Sports injuries as reversible involution: a novel approach to rehabilitation and readaptation - Rojas-Valverde, D.; Herrera-González, E.; Bonilla, D. A. (Frontiers in Sports and Active Living, 2025)
This perspective article discusses the notions of reversible involution in sports injuries and offers an innovative operational framework for rehabilitation that we expect to help with the athlete's readaptation process. Injuries have traditionally been managed by relieving the symptoms and recovery, but physiological regulation based on the allostasis-interoception model suggests that these injuries are dynamic and reversible. This reconceptualization leads to a holistic approach beyond recovery, allowing athletes to have an optimally functioning physiology. The model emphasizes on individualized rehabilitation and readaptation approaches considering the complexity of sports injuries. Under the proposed framework, rehabilitation involves treating the immediate consequences of injury and attending to physical, physiological, psychological, technical, and tactical changes by encouraging holistic attention. By treating sports injuries as reversible involution, this framework supports a multifaceted approach to rehabilitation and readaptation, where recovery relates to physiological changes reflecting interactivity between an individual's potential for healing. This approach aims to move beyond the fixed paradigms in sports medicine by providing a multidimension vision for optimizing the process of rehabilitation to accelerate athletes` health and well-being after injuries during sport-related activities.